Sistem Informasi Berbasis Website Sebagai Media Informasi di SD Tambang Kecamatan Pudak Kabupaten Ponorogo - Jamilah Karaman; Wawan Trisnadi Putra; Syeda Aliya; Ryan Erlangga Ardiansyah; Wima Alif Harianto; Wisnu Suryo Kuncoro; Vega Satria; Sholeh Khasan (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2025)
SDN Tambang is a public elementary school located in Tambang Village, Pudak District, Ponorogo Regency, East Java. This school is committed to providing quality education for children in rural environments. SDN Tambang continues to strive to develop the potential of every student through an innovative and inspiring learning process. However, the rapid development of information technology requires modernization of school administration and communication systems. Therefore, this article aims to explain the process of creating a website-based information system designed to support operational activities and transparency at SDN Tambang. In creating a website-based information system for SDN Tambang, the method used is descriptive qualitative. This system aims to facilitate access to information for students, parents and the wider community, by providing various features such as school profiles, academic information and school activities.